PERAN GURU DALAM MENGATASI KESULITAN BELAJAR PESERTA DIDIK SEKOLAH DASAR PADA MUATAN PELAJARAN MATEMATIKA MATERI SOAL CERITA - Della Purnamasari; Titania Dhiya Ulhaq; Mohamad Hafidz Eko Saputro; Arita Marini (Bajang Institute, 2023)
The method used in this research is a descriptive qualitative method. Qualitative method is a method that focuses on in-depth observations with the aim of producing a more comprehensive study of the role of teachers in overcoming student learning difficulties in math subject matter in story problems. The data collection technique used is descriptive analysis technique using literature study. In the validity test, researchers used data source triangulation. The results showed that teachers made efforts to overcome math learning difficulties in story problem material by increasing students' literacy skills, using appropriate learning tools or media, increasing practice in the form of story problem material, providing motivation to students, and collaborating with parents